Opportunistic cognitive radio network with primary user activity model - Mohamad, Mas Haslinda (2019)
A Cognitive radio (CR) network is the solution to increase spectrum utilization in wireless systems. The main objective of CR is to get the best frequency that is not in use based on its ability to detect the environment. The CR allows the secondary user (SU) to operate in a licensed spectrum without interfering with the primary user (PU). The SU can remain on the spectrum without reducing the transmission power levels. The CR performance is limited by interference from both PU and other CRs. Most previous studies analysed interference through different fading model. The interference to PU was usually measured as the quantity of SUs signal power at the primary receiver. Very few study evaluates temporal interference by considering spectrum occupancy in terms of time used in the spectrum. Therefore, the opportunistic access of CR to the PU network by considering the temporal interference is the main focus of the research.